2022
DOI: 10.24875/ric.21000404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tocilizumab in Mortality among Patients with Severe and Critical Covid-19: Experience in a Third-Level Medical Center

Abstract: Background: Trials evaluating safety and efficacy of tocilizumab in coronavirus disease 19 show contradictory results. Objective: The objective of the study was to evaluate the effect of tocilizumab in hospital mortality among patients with severe COVID-19 in a third-level medical center. Methods: This prospective cohort study included patients with severe and critical COVID-19. Primary outcome was death during hospitalization. Secondary outcomes included invasive mechanical ventilation (IMV), days on IMV, ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In multivariate analysis, male sex (aOR 7.1, 95%CI 1.1-46.0, p < 0.05), D-dimer levels > 1000 ng/mL (aOR 9.0, 95%CI 1.6-49.1, p < 0.05) and RT-PCR Ct values ≤ 24 (aOR 14.3, 95%CI 2.0-101.5, p < 0.01) were independently associated with the primary outcome. Results are summarized in Table 1 24,25 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In multivariate analysis, male sex (aOR 7.1, 95%CI 1.1-46.0, p < 0.05), D-dimer levels > 1000 ng/mL (aOR 9.0, 95%CI 1.6-49.1, p < 0.05) and RT-PCR Ct values ≤ 24 (aOR 14.3, 95%CI 2.0-101.5, p < 0.01) were independently associated with the primary outcome. Results are summarized in Table 1 24,25 .…”
Section: Resultsmentioning
confidence: 99%
“…Because age was also included in the model, the Nutri-CoV score (which uses age and pulse oximetry data for assessment) was not included in the logistic regression model. Since tocilizumab prescription was not standardized at any point during the study period and may be susceptible to selection bias 24 , it was not included in the logistic regression model. Because steroids are known to reduce COVID-19 associated mortality 25 , the variable was included in the logistic regression model.…”
Section: Discussionmentioning
confidence: 99%
“…One of them was a prospective cohort study that included 99 patients with severe and critical COVID-19 for the purpose of assessing the effect of tocilizumab on hospital mortality in severe and critical COVID-19 patients in a third-level medical center. The study found no differences between groups and mortality and concluded that tocilizumab was not associated with decreased hospital mortality [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although in Mexico research was done with a mixture of ivermectin, azithromycin, montelukast, and acetylsalicylic acid [52], ours is the first report of a wide drug mixture with pirfenidone + NTZ and colchicine. Even more, different schemes have been used in Mexico City to treat COVID-19, but besides the fact that these options are very expensive, they are not associated with decreased hospital mortality [53,54].…”
Section: Discussionmentioning
confidence: 99%